UPAYA GURU MENGATASI KESULITAN PEMAHAMAN KONSEP MATEMATIKA MATERI PENJUMLAHAN DAN PENGURANGAN BERSUSUN - Nuril Ainularifin; Mahmudah, Istiyati (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2023)
One branch of science that cannot be separated from human life is mathematics. However, quite a few students have difficulty understanding mathematical concepts. In this case the role of the teacher is very important to provide solutions to these problems. The purpose of this research is to determine the teacher's efforts to overcome difficulties in understanding mathematical concepts in addition and subtraction materials in class II MIN 2 Palangka Raya City. The method used in this research is a descriptive method with a qualitative approach. The subject of this research was the homeroom teacher of class II MIN 2 Palangka Raya City who taught mathematics subjects. This research uses observation, interviews and documentation techniques to collect data. The results of the research show that there are six efforts made by teachers to overcome students' difficulties in understanding the concept of sequential addition and subtraction material. These six efforts include: (1) Teacher before learning. Teacher ensures student readiness first; (2) Use of concrete media or teaching aids that are relevant to the teaching material; (3) Providing Assignments According to Students' Level of Thinking; (4) The teacher gives students freedom to learn and solve problems with and (5) Eliminates students' fear by taking an approach. Through these efforts, students' difficulties can be handled well so that students will further develop in understanding mathematics.